The Protection of Indonesian Indigenous Heritage in the International Conventions and Their Implication toward Indonesian Law - Irma Rachmawati Maruf (SAMPURASUN, 2015)
As an archipelago,  Indonesia consists of 17.507 islands. The regions of Indonesia have some of their indigenous ethnic groups.  However, in the light of the geographical aspect, Indonesia has 128 ethnics groups which have different cultures. Meanwhile, since the end of 1990s, the topic of genetic resources, traditional knowledge and Indigenous heritage ambit of Intellectual property discussions.  Batik and Angklung  are Indonesian Indigenous heritage which have been acknowledged by UNESCO as Intangible Cultural Heritage. One of the purposes of the acknowledgment is  to avoid  any claim from another country which has the same culture. Besides batik and angklung, there are so many indigenous heritages that  have not been acknowledged as Intangible Cultural Heritage. Due to this condition, the research is made to know what the protection should be given by law to Indigenous heritage in international law perspective. There is also how the implementation of International convention to Indonesian law can protect and maintain the cultural heritage.The method used in this study is a juridical normative with the specifications of analytical description. The research was conducted by collecting primary, secondary and tertiary legal materials through library and field research, and then analyzed with qualitative method.Based on the results of this study, it is revealed that: Firstly, the legal basis of the application of the Implementation of Protection of Indonesian Indigenous heritage have been already very relevant but still insufficient in implementation. Hence, it is not impossible that   Indonesian  government can take  economic advantages of Indigenous Heritage.  Secondly, there are various forms  of Legal protection of Indigenous Heritage, these are Law of Intellectual Property Right and Legal Protection besides Intellectual Property.Keyword : Indigenous Heritage, Intangible Cultural Heritage, Intelectual Property Right Law.